Molecular Characterization of Wild Type Measles Virus from Adult Patients in Northern China, 2014. (April 2016) - Xu, Wen; Zhang, Ming-Xiang; Qin, En-Qiang; Yan, Ying-Chun; Li, Feng-Yi; Xu, Zhe; Tian, Xia; Fan, Rong; Tu, Bo; Chen, Wei-Wei; Zhao, Min
Highlights: The patients of the 2013-2014 measles outbreaks in North China were mainly adults. The same viruses circulated between Beijing, Shenyang, Hong Kong, Taiwan and Berlin. Migration of adult workers could play an important role in these outbreaks. Abstract: Objectives: In this study, we studied the N and H genes from wild type measles viruses (MeVs) isolated during the 2013-2014 outbreak. Methods: Clinical samples were collected, and the genotyping, phylogenetic analysis were performed. Results: The vaccination rate of the study population was 4%. Genotype H1a was the predominant genotype. Wild type viruses were classified into clusters A and B, C and may have different origins. N-450 sequences from wild type viruses were highly homologous with, and likely evolved from MeVs circulating in Tianjing and Henan in 2012. MVs/Shenyang.CHN/18.14/3 could have evolved from MeVs from Liaoning, Beijing, Hebei, Heilongjiang, Henan, Jilin, and Tianjin. Our data suggested that one or more of the same viruses circulated between Beijing, Shenyang, Hong Kong, Taiwan and Berlin. Conclusions: Important factors contributing to outbreaks could include weak vaccination coverage, poor vaccination strategies, and migration of adult workers between cities, countries, and from rural areas to urban areas.